PERSEPSI WISATAWAN TERHADAP OLEH-OLEH KERIPIK CABE DI KOTA DUMAI - Mira Yuastrida; Siti Sofro Sidiq (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This study aims to prove the perception of tourists for souvenirs chili chips in Dumai City. This research is a survey with a census method, with a total sample of 36 respondents. Data analysis was performed by testing multiple linear regression using SPSS version 16. The variable in this study is the chips taste chili, chili chips price and tourist satisfaction. The results showed that the variables flavor chili chips proved to affect the perception of tourists, while the price variable chili chips and tourist satisfaction proved to have no effect on the perception of tourists on souvenirs chili chips in Dumai City. Simultaneously variable chips taste chili, chili chips price and tourist satisfaction together influence the perception of tourists. The coefficient of determination (R2) of 0.628 or 62.8%. This shows that the three independent variables (flavor chips chili, chili chips price and tourist satisfaction) jointly able to explain to the dependent variable was 62.8%, while the remaining 37.2% can be explained by other variables that are not described in the study this.Keywords : Perception of Tourists, Flavor Chips Chili, Chili Chips Price, Satisfaction Rating